2008
DOI: 10.1038/onc.2008.215
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional gene regulation by HuR promotes a more tumorigenic phenotype

Abstract: In a breast tumor xenograft model, the MCT-1 oncogene increases the in vivo tumorgenicity of MCF7 cells by promoting angiogenesis and inhibiting apoptosis. Increases in the tumor microvascular density are accompanied by a strong reduction in the levels of the angiogenesis inhibitor thrombospondin-1 (TSP1), but the mechanisms underlying this process are unknown. We show that TSP1 expression is controlled, at least in part, by post-transcriptional events. Using RNA interference to knock down the expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
105
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 47 publications
(73 reference statements)
5
105
1
Order By: Relevance
“…33,34 As previously mentioned HuR has been described to stabilize TSP1 and VEGF mRNA resulting in greater levels and increased protein expression. 21,27 In contradistinction to published reports of HuR stabilization of VEGF mRNA, our findings indicate that under conditions of HuR overexpression, there are decreases in both VEGF mRNA and protein levels. The reasons for this discrepancy are presently unknown, though the results may be dependent upon levels of HuR overexpression and hypoxia.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…33,34 As previously mentioned HuR has been described to stabilize TSP1 and VEGF mRNA resulting in greater levels and increased protein expression. 21,27 In contradistinction to published reports of HuR stabilization of VEGF mRNA, our findings indicate that under conditions of HuR overexpression, there are decreases in both VEGF mRNA and protein levels. The reasons for this discrepancy are presently unknown, though the results may be dependent upon levels of HuR overexpression and hypoxia.…”
Section: Discussioncontrasting
confidence: 56%
“…TSP1 is a well known anti-angiogenetic factor and has been described to be regulated by HuR. 27 Enumeration of angiogenesis by CD34 staining confirmed that HuR overexpression resulted in significant decreases in new blood vessel formation. This decrease in neovascularization may, in part, explain why tumors formed by HA-HuR overexpression were much smaller than EV controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other AUBPs such as tristetraprolin (TTP) and additional members of the TTP family have been shown to have similar effects, while still other AUBPs such as HuR appear to promote enhanced transcript stability (reviewed in [14]). Very recently, HuR has been shown to bind to the TSP-1 mRNA and increase its stability, although the site of this interaction was not characterized [17]. The conditions under which AUBPs such as AUF1 and HuR bind to TSP-1 mRNA in granulosa cells, and whether such interactions are regulated by IGFs or other factors relevant to the growth and differentiation of granulosa or other follicular cells, remains a subject of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these elements mediates a strong destabilizing effect on TSP-1 mRNA transcripts, resulting in a rapid reduction of TSP-1 mRNA. Recently, HuR, an AUBP known to stabilize target mRNAs and enhance their translation, has been shown to associate with the TSP-1 mRNA in breast cancer cells, although the HuR binding site on the mRNA was not identified in that study [17]. The stability of the TSP-1 mRNA is also influenced by cellular expression of the oncogene c-myc, although this has not been shown to involve ARE-medicated decay [18].…”
mentioning
confidence: 89%